(untitled) (Research, Society and Development, 2022)
Didactic is considered essential for the training of teachers and as perspectives of disciplines related to the discipline can highlight paths for its constant improvement. Thus, this work aimed to understand the perceptions of Undergraduates in Biological Sciences related to the Didactics discipline and its importance for teacher education in Higher Education Institution located in the city of Uruçuí-PI. The research is of the quali-quantitative type, it has an observational nature. For its realization, it had the participation of 28 students who attended from the sixth period. From the analysis of the participants’ responses, it was observed that the main expectation of students in relation to the subject was to know new methodologies to guide them in the classroom, and that most of the sample group see the subject as fundamental for their training. Regarding the skills acquired while studying Didactics, the most mentioned for the ability to prepare and apply teaching plans, observing their constituent elements. Difficulty to reflect the diversified learning assessment strategies was also verified. Given the results obtained in this study, we point out that many students enter teaching courses for lack of opportunity to enter another desired course, whose main reason is the Brazilian educational scenario, where teachers are undervalued, neglected and disrespected. It is essential to value professionals for the quality of teaching. Finally, we report that a greater motivation of undergraduates in the course and Didactic discipline was to learn about new methodologies to be used in the classroom in their teaching practice. Thus, it is important to take advantage of this interest and motivation of students, and from it to present and encourage the use of different methodologies in the school context, which will thus provide greater support to the teacher in training, so that they are prepared for the diversity of students who arrive in the classroom. We also specify the need for further studies, including teachers who work in basic achievement education, also evaluate the importance of the discipline in the school context of these teachers.